The Two Sons Of Prophet Adam(AS) - "Khan, saniyasnain" (China; Goodword Books, 2024)
Introduce your child to the captivating story of the two sons of Prophet Adam (A.S) through this beautifully illustrated board book. The story uses simple and engaging language to share an important lesson about choices, consequences, and morality. Filled with vibrant illustrations, the book captures young readers$1 (Battention and brings the story to life. Designed especially for toddlers and preschoolers, the sturdy board book format is perfect for little hands and repeated reading. This story helps children understand important values such as honesty, kindness, and making good decisions. It$1 (Bs an ideal way for families to nurture early spiritual growth and start meaningful conversations about right and wrong.s
Keywords: Prophets story